2011
DOI: 10.1111/j.1740-8709.2011.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of inappropriate complementary feeding practices in young children in Nepal: secondary data analysis of Demographic and Health Survey 2006

Abstract: Inappropriate complementary feeding increases the risk of undernutrition, illness and mortality in infants and children. This study uses a subsample of 1428 children of 6-23 months from Nepal Demographic and Health Survey (NDHS), 2006. The 2006 NDHS was a multistage cluster sample survey. The complementary feeding indicators were estimated according to the 2008 World Health Organization recommendations. The rate of introduction of solid, semi-solid or soft foods to infants aged 6-8 months was 70%. Minimum meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

53
139
13
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(208 citation statements)
references
References 9 publications
53
139
13
3
Order By: Relevance
“…Accordingly, mothers with primary, and no formal education were 3.32 and 4.78 times more likely to practice feeding inadequate dietary diversity to their children than those educated above secondary level (AOR = 3.32, 95% CI: 2.01, 5.21) and (AOR = 4.78, 95% CI: 2.55, 8.95). This finding is in line with findings from other studies [27,28,29,30]. This implies that parental education plays an important role in meeting the minimum dietary diversity standards.…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, mothers with primary, and no formal education were 3.32 and 4.78 times more likely to practice feeding inadequate dietary diversity to their children than those educated above secondary level (AOR = 3.32, 95% CI: 2.01, 5.21) and (AOR = 4.78, 95% CI: 2.55, 8.95). This finding is in line with findings from other studies [27,28,29,30]. This implies that parental education plays an important role in meeting the minimum dietary diversity standards.…”
Section: Discussionsupporting
confidence: 83%
“…The results revealed that the prevalence of appropriate complementary feeding was only 13.8 % which is similar to what was reported from Northern Ethiopia, Sri Lanka, Nepal and Tanzania Bangladesh, Zambia, and [17][18][19][20]. This indicates the general low level of appropriate complementary feeding practices in many countries including Ghana.…”
Section: Discussionsupporting
confidence: 71%
“…This study revealed that there was no association between frequency of antenatal care (ANC) visits and appropriate complementary feeding practice and same was reported in Northern Ethiopia [17] but that disagrees with other studies in Nepal, India and Sri Lanka [18,19,24] where inadequate antenatal care was associated with inappropriate complementary feeding. The finding in our study could imply that appropriate complementary feeding messages were either not being given to mothers by health professionals during antenatal or there was little variation in ANC attendance among the mothers.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In Table 3, the prevalence of HHFI was also 55 [23][24][25][26] Global foods prices have increased by more than 10% along with social, political and environmental vulnerabilities adversely affecting food and nutrition security throughout South Asian regions. 27 In this study, approximately 36.3% children age 6-23 months were estimated to be food insecure.…”
Section: Prevalence Of Hhfi (Bivariate Analysis Based On Chisquare Test)mentioning
confidence: 99%